C-Reactive Protein and Other Circulating Markers of Inflammation in the Prediction of Coronary Heart Disease - Danesh, John; Wheeler, Jeremy G; Hirschfield, Gideon M; Eda, Shinichi; Eiriksdottir, Gudny; Rumley, Ann; Lowe, Gordon D.O; Pepys, Mark B; Gudnason, Vilmundur (The New England journal of medicine, 2004)
This large, prospective study calls into question the value of the C-reactive protein (CRP) concentration in the prediction of coronary events. In contrast to previous research, this study found that the strength of the CRP concentration as a predictor is relatively moderate and that it adds little to the predictive value of standard coronary risk factors, such as the cholesterol concentration, smoking status, and blood pressure. This large study calls into question the value of CRP in the prediction of coronary events. Since atherosclerosis may, in part, be an inflammatory disease, 1 circulating factors related to inflammation may be predictors of cardiovascular disease in general populations. 2 A recent statement from the Centers for Disease Control and Prevention and the American Heart Association concluded that it is reasonable to measure C-reactive protein, a sensitive circulating marker of inflammation, as an adjunct to the measurement of established risk factors in order to assess the risk of coronary heart disease. 3 The report acknowledged, however, that the epidemiologic data to support this view were not entirely consistent and recommended that larger prospective studies be conducted to improve . . .